RENEWAL OF BUSES AND REGISTRATION OF NEW BUSES IN THE SLOVAK REPUBLIC AND THE CZECH REPUBLIC - Gnap, Jozef; Dočkalik, Marek (Journal of Applied Engineering Science, 2022)
The use of alternative fuels and the use of vehicles meeting the strictest emission standards can contribute to improving the impact of road transport on the environment. Therefore, it is also very important to restore buses, which can affect the environment in cities to a certain extent. Achieving an increase in the number and share of ecological buses is possible through several tools. The contribution is focused on the analysis of the EU directive on the support of ecological and energy-saving road transport vehicles and the study of the number and share of ecological buses in European countries, and the data for the Slovak Republic and the Czech Republic, which can also be compared for the same period, are processed in more detail. Due to the growth rate of the number of ecological buses during the period under review, it can be seen that in the Slovak Republic it is definitely necessary to increase the number and the proportion of buses that have a more favourable impact on the environment and are considered ecological.
Keywords: environment, buses, EU directive, standards